1993
DOI: 10.1056/nejm199307013290102
|View full text |Cite
|
Sign up to set email alerts
|

Cat Scratch Disease in Connecticut -- Epidemiology, Risk Factors, and Evaluation of a New Diagnostic Test

Abstract: Cat scratch disease is strongly associated with owning a kitten, and fleas may be involved in its transmission. The serologic test for rochalimaea may be useful diagnostically, and our results suggest an etiologic role for this genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
295
3
21

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(334 citation statements)
references
References 20 publications
15
295
3
21
Order By: Relevance
“…Although the climate in Thailand is hot and humid throughout the year, the positive rate of B. henselae in apparently healthy individuals was almost the same as the prevalence in other countries [1,5,8,17,18,[20][21][22]. The exception is a report showing a high incidence (30%) in healthy German individuals [19].…”
mentioning
confidence: 73%
“…Although the climate in Thailand is hot and humid throughout the year, the positive rate of B. henselae in apparently healthy individuals was almost the same as the prevalence in other countries [1,5,8,17,18,[20][21][22]. The exception is a report showing a high incidence (30%) in healthy German individuals [19].…”
mentioning
confidence: 73%
“…henselae infection were temporally related to a tick exposure in the United States (reviewed in [2]). Tick exposure was reported as a risk factor associated with CSD in humans ( 39 ). Similarly, tick exposure was determined to be a risk factor associated with B .…”
Section: Beyond the Fleas: New Emerging Vectorsmentioning
confidence: 99%
“…Recent investigations suggested that a fastidious bacterium Bartonella henselae is a causative agent for bacillary angiomatosis (BA) and bacillary peliosis (BP) in HIV-positive patients [18,21,29]. Furthermore, serological investigations strongly suggested that B. henselae is a causative agent of CSD [25,31] and the organism was isolated from typical CSD patients in immunocompetent status [10].…”
Section: Indirect Immunofluorescent Antibody Test For B Henselaementioning
confidence: 99%